2007
DOI: 10.1080/00071660701244738
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of taste-active components of meat by dietary leucine

Abstract: 1. Regulation of meat taste is one effective method for improvement of meat quality. In this study, effects of dietary leucine (Leu) content on taste-active components, especially free glutamate (Glu), in meat were investigated. 2. Broiler chickens (28 d old) were fed on diets with graded dietary Leu content (100, 130 or 150% of Leu requirement in NRC, 1994) for 10 d before marketing. Taste-active components of meat (free amino acids and ATP metabolites) and sensory score of meat soup were estimated. 3. Free G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 37 publications
(45 reference statements)
1
17
0
1
Order By: Relevance
“…In contrast, our previous results suggested that nutrient treatments such as restriction feeding or administration of branched‐chain amino acids (BCAA) to chickens affected the Glu content in muscle and hence the taste of meat (Fujimura et al . 2001; Imanari et al . 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, our previous results suggested that nutrient treatments such as restriction feeding or administration of branched‐chain amino acids (BCAA) to chickens affected the Glu content in muscle and hence the taste of meat (Fujimura et al . 2001; Imanari et al . 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The free amino acid levels in muscle were measured as described by Imanari et al . (2007) using an amino acid analyser (JLC‐500/V; JEOL, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Muscle extracts were prepared as described by Imanari et al (2007). The muscles were homogenized in 10% perchloric acid with a high-speed homogenizer (Ultra-turrax T25 basic, Ikawerke, Staufen, Germany).…”
Section: Free Amino Acid and Dipeptide Contentmentioning
confidence: 99%
“…Muscle and liver extracts were prepared as described by Imanari et al (2007). The muscles and livers were homogenized in 10% perchloric acid with a highspeed homogenizer (Ultra-turrax T25 basic; Ikawerke, Staufen, Germany).…”
Section: Preparation Of Muscle and Liver Extractsmentioning
confidence: 99%